(untitled) (American Journal of Business Management, Economics and Banking, 2025)
Regional tourism resources, including natural, cultural, and historical objects, are an important component of the tourism industry. These resources play a significant role in developing the region’s economy, increasing employment, and preserving the national heritage. This article analyses the existing potential of regional tourism resources and their future development prospects.